Missed cleavage opportunities by FEN1 lead to Okazaki fragment maturation via the long-flap pathway. Issue 6 (6th February 2018) - Zaher, Manal S; Rashid, Fahad; Song, Bo; Joudeh, Luay I; Sobhy, Mohamed A; Tehseen, Muhammad; Hingorani, Manju M; Hamdan, Samir M
Abstract: RNA–DNA hybrid primers synthesized by low fidelity DNA polymerase α to initiate eukaryotic lagging strand synthesis must be removed efficiently during Okazaki fragment (OF) maturation to complete DNA replication. In this process, each OF primer is displaced and the resulting 5′-single-stranded flap is cleaved by structure-specific 5′-nucleases, mainly Flap Endonuclease 1 (FEN1), to generate a ligatable nick. At least two models have been proposed to describe primer removal, namely short- and long-flap pathways that involve FEN1 or FEN1 along with Replication Protein A (RPA) and Dna2 helicase/nuclease, respectively. We addressed the question of pathway choice by studying the kinetic mechanism of FEN1 action on short- and long-flap DNA substrates. Using single molecule FRET and rapid quench-flow bulk cleavage assays, we showed that unlike short-flap substrates, which are bound, bent and cleaved within the first encounter between FEN1 and DNA, long-flap substrates can escape cleavage even after DNA binding and bending. Notably, FEN1 can access both substrates in the presence of RPA, but bending and cleavage of long-flap DNA is specifically inhibited. We propose that FEN1 attempts to process both short and long flaps, but occasional missed cleavage of the latter allows RPA binding and triggers the long-flap OF maturation pathway.